2018
DOI: 10.1242/jeb.191056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental manipulation of hematocrit on avian flight performance in high and low altitude conditions

Abstract: Despite widely held assumptions that hematocrit (Hct) is a key determinant of aerobic capacity and exercise performance, this relationship has not often been tested rigorously in birds and results to date are mixed. Migration in birds involves high-intensity exercise for long durations at various altitudes. Therefore, it provides a good model system to examine the effect of Hct on flight performance and physiological responses of exercise at high altitude. We treated yellow-rumped warblers (Setophaga coronata)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
(98 reference statements)
2
25
0
Order By: Relevance
“…and Clemens found that birds that reside at high altitude year round have high Hct and Hb relative to lowland birds, and that Hb is correlated with altitude in both high altitude residents and elevational migrants 19,21 , despite the fact that Hct and Hb are relatively plastic traits. It is also well known that Hct and Hb is increased prior to and during long distance migration in birds 10,16,22 . Furthermore, Hct and Hb are also highly repeatable within individuals and within species 23,24 .…”
Section: Introductionmentioning
confidence: 97%
“…and Clemens found that birds that reside at high altitude year round have high Hct and Hb relative to lowland birds, and that Hb is correlated with altitude in both high altitude residents and elevational migrants 19,21 , despite the fact that Hct and Hb are relatively plastic traits. It is also well known that Hct and Hb is increased prior to and during long distance migration in birds 10,16,22 . Furthermore, Hct and Hb are also highly repeatable within individuals and within species 23,24 .…”
Section: Introductionmentioning
confidence: 97%
“…Species and populations of birds and mammals that are regularly exposed to high altitudes have adaptations to enhance oxygen delivery, including greater HVR and greater oxygen-carrying capacity of the blood (reviewed in Butler, 2010;Scott, 2011;Ivy and Scott, 2014;Scott et al, 2015b). More recent research has shown that high altitude can also act as a strong selection pressure for greater oxidative capacity at the cellular level across both birds (Dawson et al, 2016;Yap et al, 2018;Hao et al, 2019) and mammals (Storz, 2007;McClelland and Scott, 2018). Despite these shared features, the advantages of the avian lung, hemoglobin with a high oxygen affinity and insensitivity to hypocapnia, triumph.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be an adaptation necessary to sustain the high oxygen demands of flight (Tucker, 1970), rather than a response to hypobaric hypoxia per se. It is yet to be shown if greater fatty acid metabolism is beneficial at high altitudes, given the higher oxidative cost of metabolizing fatty acids; oxidizing lipids becomes increasingly expensive relative to glycogen with increasing altitude (Melzer, 2011;Yap et al, 2018). Enzymes involved in the metabolism of fatty acids were not found to vary across the locomotor muscles of high-and low-altitude populations of torrent duck (Dawson et al, 2016).…”
Section: Skeletal Muscle Oxygen Delivery and Usementioning
confidence: 97%
“…For example, flight performance was higher in warblers flying at low altitudes when hematocrit was experimentally enhanced but was lower when those same individuals flew at high altitudes, suggesting a cost to manipulating hematocrit (Yap et al, 2018).…”
Section: Introductionmentioning
confidence: 99%